Pro-Angiogenic Effects of Natural Antioxidants Extracted from Mango Leaf, Olive Leaf and Red Grape Pomace over Endothelial Colony-Forming Cells - Ismael Sánchez-Gomar; Josefa Benítez-Camacho; Cristina Cejudo-Bastante; Lourdes Casas; Rafael Moreno-Luna; Casimiro Mantell; Mª Carmen Durán-Ruiz (MDPI AG, 2022)
Cardiovascular diseases remain the leading cause of death worldwide, mainly triggered by the formation of atherosclerotic plaques that reduce blood flow. Angiogenic cell therapy based on endothelial colony forming cells (ECFCs) constitutes a promising alternative to promote vascular revascularization; however, under the oxidative environment that prevails in ischemic areas, these cells become impaired. Thus, it is necessary to investigate strategies to enhance their regenerative properties. Antioxidant substances, such as polyphenols, have been shown to be useful for this purpose. In the current study we evaluated the potential of mango leaves, olive leaves and red grape pomace extracts, rich in polyphenols, to promote ECFC reparative effects. For this, aqueous and ethanolic extracts of the aforementioned raw materials were obtained by pressurized liquid extraction (PLE). After evaluating the polyphenol content and the antioxidant activity, in vitro assays were carried out, and we found that ethanolic extracts at low concentrations improved angiogenic capacities of ECFCs and reduced proliferation, apoptosis, and the inflammatory response of these cells. Overall, mango leaves ethanolic extract provided the most promising results, but all three extracts ameliorated the functionality of ECFCs.